THE ROLE OF MODERN TECHNOLOGIES IN THE CONDUCT OF SPIRITUAL AND EDUCATIONAL ACTIVITIES. (ON THE EXAMPLE OF MULTIMEDIA TOOLS) - Pardaev Sobit Abduvali oglu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article deals with the ongoing reforms in the process of spiritual and educational work, as well as the use of modern technologies, types of modern technologies.